Communication networks : - Leon-Garcia, Alberto (McGraw-Hill, 2000)
This new text is designed for introductory courses in communications in either electrical engineering or computer science programs. It can be used by undergraduate or first year graduate level programs. Addressing networks from a top-down approach, this text shows students the big picture of networks in general so that they may see how the various parts of the network fit in to the picture. The book is organized into six sections that progressively consider the networking functions in greater level of detail. The book presents a balanced view of all important elements of networking and is organized so that all relevant topics can be covered at some minimum level of detail.